2019
DOI: 10.3390/molecules24224153
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MicroRNA-155 and Its Related Genes Expression by Inositol Hexaphosphate in Colon Cancer Cells

Abstract: Inositol hexaphosphate (IP6), a natural dietary component, has been found as an antitumor agent by stimulating apoptosis and inhibiting cancer cell proliferation, their migration, and metastasis in diverse cancers including colon cancer. However, molecular mechanisms of its action have not been well understood. In recent years, microRNAs (miRNAs) have been reported to play important roles in a broad range of biologic processes, such as cell growth, proliferation, apoptosis, or autophagy. These small noncoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The reduction in mycotoxin-induced apoptosis by IP6 demonstrates its potent antioxidant effect, since ROS generation is directly linked to apoptosis activation. Similar modulation of cell viability has been observed in inflammatory bowel studies [19,38,39]. IP6 induced a significant reduction in cox-2 expression compared to the explants exposed to all mycotoxin treatments.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The reduction in mycotoxin-induced apoptosis by IP6 demonstrates its potent antioxidant effect, since ROS generation is directly linked to apoptosis activation. Similar modulation of cell viability has been observed in inflammatory bowel studies [19,38,39]. IP6 induced a significant reduction in cox-2 expression compared to the explants exposed to all mycotoxin treatments.…”
Section: Discussionsupporting
confidence: 82%
“…The reduction in cox-2 expression observed in the present study can be associated with the ability of IP6 to inhibit ROS production, lipid peroxidation, and inflammatory stimuli [40] induced by DON and FB 1 . Moreover, studies have demonstrated that IP6 reduces the expression of cox-2 by inhibition of p38 MAPK, as well as the conversion of arachidonic acid into prostaglandins and suppression of β-catenin activity [19,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can induce and promote the inflammation process. In vivo and in vitro studies have demonstrated that PA has a chemopreventive action in CRC due to its antiinflammatory property (51)(52)(53) . Our results showed that the serum expressions of TNF-α, IL-1β and IL-6 in the MG were significantly higher than those in the CG, which indicated that inflammation played a critical role in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above effects, phytic acid treatment of cells was also found to increase the expression of I-κB [ 102 ], an inhibitor of NF-κB, which was indicated above to be a mediator of both inflammation and cell proliferation. More recently, a study also showed that phytic acid treatment of Caco-2 cells was able to reverse the pro-inflammatory effects of the treatment with inflammatory mediators through the down-regulation of the expression of inducible nitric oxide synthase (iNOS) [ 103 ], an enzyme whose over-expression was observed in patients with IBD [ 104 ]. Furthermore, in vitro γ-tocotrienol treatment was shown to inhibit the activity of NF-κB, leading to a decrease in the expression of pro-inflammatory and pro-proliferative genes, including cyclo-oxygenase 2, cyclin D1 and c-myc [ 105 , 106 ].…”
Section: Other Potential Oxidative-stress-related Mechanisms For Tmentioning
confidence: 99%